Liver and spleen transient elastography predicts portal hypertension in patients with chronic liver disease: a prospective cohort study. Issue 1 (December 2015) - Zykus, Romanas; Jonaitis, Laimas; Petrenkienė, Vitalija; Pranculis, Andrius; Kupčinskas, Limas
Abstract Background To assess correlation between liver or spleen stiffness measurement by transient elastography (TE) and hepatic venous pressure gradient (HVPG) in patients with chronic liver disease as well find optimal and rule in/rule out cut-offs for prognosis of clinically significant (CSPH) and severe (SPH) portal hypertension. Methods In this prospective study patients with different chronic liver diseases were included. TE was performed at the same day prior to HVPG measurement. HVPG was measured using catheter tip occlusion technique. Based on HVPG, patients were categorized into groups of CSPH and SPH. Cut-off values were established by applying ROC curve analysis. Results The study included 107 consecutive patients referred for HVPG measurement or transjugular liver biopsy. Successful spleen TE was performed in 99 of the patients. Liver and spleen TE strongly correlated with HVPG, r  = 0.75 andr  = 0.62, respectively. Accuracy to detect CSPH was 88.7 % for liver stiffness of 17.4 kPa and 77.7 % for spleen stiffness of 47.6 kPa. Accuracy to detect SPH was 83.1 % for liver stiffness of 20.6 kPa and 77.7 % for spleen stiffness of 50.7 kPa. Liver stiffness <11.4 kPa could rule out CSPH with 55.2 % specificity and >21.9 kPa rule in CSPH with 74.4 % sensitivity. Liver stiffness <12.1 kPa could rule out SPH with 50.0 % specificity and >35 kPa rule in SPH with 58.2 % sensitivity. Conclusions Liver and spleen stiffness correlate with HVPG and could be used to predict CSPH or SPH. Spleen elastography was not superior to liver elastography in predicting portal hypertension.